PERSEPSI PESERTA PELATIHAN DASAR TERHADAP PENGGUNAAN QUIZIZZ SEBAGAI METODE EVALUASI PEMBELAJARAN - Marsye Fera Kalahatu (Akademika : Jurnal Teknologi Pendidikan, 2021)
Quizizz is a web tool for creating interactive quiz games for use in classroom learning. It is very easy to use, interactive quizzes are made by having up to 5 answer choices including the correct answer. Evaluation with the quizizz method is used to measure the understanding of basic training participants before and after the learning process. With this quizizz method, training participants will enjoy evaluating learning more, because this method is as fun as playing games. But of course it cannot be denied that every application has advantages and disadvantages, including this quizizz application. The use of this quizizz application online is very dependent on the availability of the internet network. This paper describes the perceptions of basic training participants (Latsar) on the use of quizizz as a learning evaluation method, especially in anti-corruption training. The learning evaluation using quizizz was very effective, where the pre-test results related to the participants' understanding of anti-corruption material were 44%, and the post-test results increased to 71% or an increase of 27%. That means that the quizizz learning evaluation method is able to improve the results of the evaluation, concentration and motivation of the participants when they are in the learning evaluation process.